Behavioral drive and morphological amplification of an aggressive display - Hastings, Philip A. (Frontiers in Ethology, 2023)
The evolution of conspicuous morphology and related displays is often ascribed to their role in sexual selection. The context of displays together with the phylogenetic sequence of morphological and behavioral innovations provides insight into their evolution. Do conspicuous features function in mate attraction and/or aggression and does a behavioral display evolve before or after the morphological feature most evident in the display? These questions were explored for a unique display and dorsal fin feature in a clade of blenniiform fishes for which both courtship and aggressive displays are known. The anterior dorsal-fin spines of the Spikefin Blenny, Coralliozetus rosenblatti, are elongate. It has a unique courtship display but the fin is held statically erect similar to congeners. This and other species of Coralliozetus, perform a unique aggressive display, the "fin flag", in which the anterior dorsal fin is waved laterally when encountering conspecifics. The spike-like dorsal fin of C. rosenblatti and its exaggerated lateral movements render this display especially conspicuous. In addition it performs the fin flag more than twice as often as congeners. Thus the dorsal fin of the Spikefin Blenny evolved to amplify an extant aggressive display consistent with the behavioral drive hypothesis that posits behavior leads to subsequent morphological evolution making displays more effective. KEY WORDS behavioral drive, displays, amplification, aggression, courtship, Chaenopsidae, Blenniiformes, Teleostei Introduction Conspicuous morphological features of animals and the behaviors displaying them are often attributed to their role in sexual selection, either for attracting mates, aggressive signaling in intraspecific interactions, or both (Andersson, 1994;Berglund et al., 1996;Laidre and Johnstone, 2013). Identifying which of these is the proper context of conspicuous displays can be inferred by observing the frequency of such displays during aggressive versus courtship interactions, but the origin of such displays and the morphology upon which they are based is more elusive. Comparison of morphology and behavior across species sharing a recent common ancestor (clades) is a valuable approach to understanding the origin and modification of both morphology and